Ke-Kriya-an pada Arsitektur Jawa - Hardiyati Hardiyati; Anita Dianingrum (ARSITEKTURA, 2021)
Development of unlimited information resulting in the loss of the diversity of architectural identity of place. Contemporary architecture develops without control and without clear concept seeds. Craftsmanship is always attached to art because in the final result there is a content of art, even though the meaning of art is always being discussed and always developing. Javanese house architecture has three important things, namely the relationship of Jiwa Cipta / wastu, resources / kalang and form / wewangunan, which are the totality of architecture. The purpose of this research is to describe the understanding of "Javanese architecture" by taking a broader perspective that will be used in this study. This relationship will be traced through the craftsmanship inherent in Javanese architectural works. The method used is field research which is a qualitative research with problems in a natural setting to interpret and interpret the observed phenomena. Craftsmanship of Javanese architectural will complement the knowledge of Javanese architecture which will enrich the identity of Indonesian architecture in accordance with the place and time travel which will always change according to human civilization. Craftsmanship in Javanese architecture produce Javanese architecture consisting of constructive and non-constructive percussion crafts that are able to provide articulation of the manufacturing process, articulation of talent / character of materials, articulation of expression of load joints articulation of material processing.